TANTANGAN DAN KENDALA IMPLEMENTASI SISTEM INFORMASI MANAJEMEN PENDIDIKAN (SIMP): MENGAPA TEKNOLOGI SAJA TIDAK CUKUP? - Windy Nurahmadani; Jusmita Raja; Sulkifli (As-Sulthan Journal of Education, 2026)
The development of information technology has brought many changes in various fields, including education. One form of utilizing this technology is the Education Management Information System (EMIS), which is used to support the management of educational data and administration more effectively. Through this system, various types of information such as student data, teacher data, and academic activities can be managed in a more structured manner. However, in practice, the implementation of EMIS does not always run as expected. Many educational institutions still face various obstacles in the implementation process. These challenges are not only related to technological aspects but also involve human resources, organizational culture, and policy support from management. This study aims to examine the various challenges that arise in the implementation of Education Management Information Systems and to explain why technology alone is not sufficient to guarantee the success of the system. This research uses a qualitative approach with a literature study method based on various journals, books, and previous studies relevant to the topic discussed. The findings show that the success of EMIS implementation is greatly influenced by user readiness, organizational support, and the existence of clear policies in system management. In other words, the presence of technology must be balanced with preparedness in various aspects so that the system can truly provide benefits for educational institutions.